Living with lymphoedema-the perspective of cancer patients: a qualitative study. - Río-González, Ángela; Molina-Rueda, Francisco; Palacios-Ceña, Domingo; Alguacil-Diego, Isabel M. (Supportive Care in Cancer, 2018)
Purpose: The aim of this study was to describe the lived experience of lymphoedema and the barriers faced by cancer sufferers receiving physiotherapy outpatient treatment.Methods: A qualitative, phenomenological study was performed. Purposeful sampling method was used. Data collection methods included unstructured and semi-structured interviews and researcher field notes. A thematic analysis was used. The study was conducted following the Consolidated Criteria for Reporting Qualitative Research guidelines.Results: Eleven patients (62.18 ± 10.14 years) (90.91% women) participated. One theme was identified with different subgroups. The main theme 'Living a life with multiple barriers'-formed by the subthemes 'Discovering physical and psychological barriers', 'Searching information', 'Building relationships' and 'Controlling expenses'-displays the daily difficulties they must face in areas such as work. The patients reported that lymphoedema is a constant emotional and physical challenge. They need to adapt their lives to their new situation, learning how to manage the lymphoedema.Conclusions: Patients considered lymphoedema as a clinical situation with multiple barriers and they found that it does alter their quality of life. These results can be applied in onco-haematology units to develop specific protocols for customers.